SERS Sensor for Human Glycated Albumin Direct Assay Based on Machine Learning Methods - Ekaterina A. Slipchenko; Irina A. Boginskaya; Robert R. Safiullin; Ilya A. Ryzhikov; Marina V. Sedova; Konstantin N. Afanasev; Natalia L. Nechaeva; Ilya N. Kurochkin; Alexander M. Merzlikin; Andrey N. Lagarkov (Chemosensors, 2022)
In this study, a non-labeled sensor system for direct determining human glycated albumin levels for medical application is proposed. Using machine learning methods applied to surface-enhanced Raman scattering (SERS) spectra of human glycated albumin and serum human albumin enabled the avoidance of complex sample preparation. By implementing linear discriminant analysis and regularized linear regression, classification and regression problems were solved based on the spectra obtained as a result of the experiment. The results show that, coupled with data augmentation and a special cross-validation procedure, the methods we employed yield better results in the corresponding tasks in comparison with popular random forest methods and the support vector method. The results show that SERS, in combination with machine learning methods, can be a powerful and effective tool for the simple and direct assay of protein mixtures.